2008
DOI: 10.1007/s11748-008-0239-6
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement in a patient with a brain tumor

Abstract: We report a case of aortic stenosis with a brain tumor in a 67-year-old man. Although he showed no clinical neurological abnormality, a computed tomography scan revealed a brain tumor. We performed aortic valve replacement under several management techniques to avoid cerebral injury. Two biochemical markers for brain injury, S-100beta and neuron-specific enolase, were measured perioperatively. The postoperative course was uneventful without neurological complication, and the biochemical markers were within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…[1][2][3][4][5] In contrast, when tumors were detected preoperatively and adequate measures were taken, surgery was completed without complications. [6][7][8] These findings suggested that intracranial evaluation before surgery using CPB and strict perioperative management are important for patients with brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In contrast, when tumors were detected preoperatively and adequate measures were taken, surgery was completed without complications. [6][7][8] These findings suggested that intracranial evaluation before surgery using CPB and strict perioperative management are important for patients with brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A team approach with the involvement of neuro-anaesthesia and neurosurgical team is recommended. Intra-operative measures to reduce the intracranial pressure including avoidance of hypercapnia and hyponatraemia, use of mannitol and steroids, and maintenance of higher perfusion pressures on cardiopulmonary bypass have been successfully employed [16].…”
Section: Discussionmentioning
confidence: 99%
“…Serum S100B (µg/L) operation (31,32). S100B upregulation varied in different parts of the brain: upregulation is highest in the penumbra region, and not in the infarct region, indicating that S100B release after a cerebral ischemia could be as a consequence of hypoxic, but not dead cells, in the penumbra.…”
Section: Discussionmentioning
confidence: 99%